2003
DOI: 10.3402/ijch.v62i1.17526
|View full text |Cite
|
Sign up to set email alerts
|

An overview of factors influencing the health of Canadian Inuit infants

Abstract: Locally driven, focused and methodologically sound epidemiological research that addresses key gaps in knowledge could lead to more appropriate and effective preventive strategies to improve health in northern communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Both the quantity and quality of living space in Nunavut are inadequate. 4,7,8 According to the 2001 Aboriginal Peoples Survey, in which overcrowding is defined as one or more persons per room in a dwelling, 54% of Inuit in Nunavut live in overcrowded conditions. 9 In the face of a birth rate that is more than twice the Canadian average, the gap between existing living space and future need is increasing rapidly.…”
Section: -5mentioning
confidence: 99%
See 1 more Smart Citation
“…Both the quantity and quality of living space in Nunavut are inadequate. 4,7,8 According to the 2001 Aboriginal Peoples Survey, in which overcrowding is defined as one or more persons per room in a dwelling, 54% of Inuit in Nunavut live in overcrowded conditions. 9 In the face of a birth rate that is more than twice the Canadian average, the gap between existing living space and future need is increasing rapidly.…”
Section: -5mentioning
confidence: 99%
“…Low socioeconomic status is associated with poor housing, and multiple logistic regression in one study showed that socioeconomic status is a stronger predictive factor for the frequency of visits to health centres. 4,12 Poor housing quality and overcrowding may be associated with, and a proxy for, more specific factors for exposure, susceptibility or resistance to infection; for example, adequacy and type of nutrition (including breastfeeding), behaviour resulting in exposure to infectious agents (e.g., within child care settings) and exposure to environmental contaminants (including tobacco smoke).…”
mentioning
confidence: 99%
“…Education, employment, income, the physical environment, housing, smoking, alcohol, and breast-feeding practises are all issues that need to be addressed in a new paradigm of preventive medicine (5). In ICC's Principles and Elements for a Comprehensive Arctic Policy al-so adds spiritual and cultural factors to the mix of defining health and well-being (6).…”
Section: Aqqaluk Lynge President Icc Greenlandmentioning
confidence: 99%
“…Inuit-based models of midwifery care have been instituted in some northern communities, this is not the dominant healthcare model in Nunavik (Jenkins et al, 2003).…”
Section: Description Of Study Area Figure 1 Map Situating Nunavik Witmentioning
confidence: 99%
“…These statistics have been attributed to a variety of factors including poor diet (related to high food prices, lack of availability and access to nutritious fresh food and an overabundance of processed, store-bought foods) and increasing rates of disease including diabetes and heart disease (Jenkins et al, 2003). Almost 60% of Nunavik's population is under twenty-five and 75% are under thirty-five years of age.…”
Section: Description Of Study Area Figure 1 Map Situating Nunavik Witmentioning
confidence: 99%